"If I've got latent TB, I would like to get rid of it": Derivation of the CARD (Constraints, Actions, Risks, and Desires) Framework informed by South African healthcare worker perspectives on latent tuberculosis treatment. - Ruvandhi R Nathavitharana (Public Library of Science (PLoS), 2021)
Background Healthcare workers (HWs) have at least twice the risk of tuberculosis (TB) compared to the general population. There is growing emphasis on latent TB infection (LTBI) in high-risk populations. Yet we know little about HWs' perspectives of LTBI testing and treatment to inform implementation in high-incidence settings. We developed a qualitative networked approach to analyze HWs' perspectives on LTBI testing and treatment. Methods We conducted 22 in-depth interviews with nurse and physician stakeholders, who had been recruited as part of a larger study evaluating TB transmission risk in HWs at Tygerberg Hospital, Cape Town, South Africa. We performed open coding to identify emergent themes and selective coding to identify relevant text citations. We used thematic analysis to inductively derive the CARD (Constraints, Actions, Risks, Desires) framework. Results All HWs desired to avoid developing TB but few felt this was actionable. Despite LTBI knowledge gaps, safety and cost concerns, most HWs reported hypothetical willingness to take LTBI treatment. The CARD framework showed that desire and action related to LTBI testing and treatment was clearly framed by the interactions between constraints, administrative action, and risk. The surprise HWs described on receiving a negative LTBI (Quantiferon-Plus) result suggests LTBI testing may recalibrate HWs' perceptions regarding the futility of actions to reduce their TB risk. Conclusions LTBI testing and treatment are acceptable to HWs and could counteract the perceived inevitability of occupational TB infection that currently may limit risk reduction action. This should be coupled with administrative leadership and infrastructural support. The CARD analytic framework is a helpful tool for implementation scientists to understand current practices within complex health systems. Application of CARD could facilitate the development of contextually-relevant interventions to address important public health problems such as occupational TB.